Exercise Identity and Spiritual Well-Being in Nursing Home Residents: Mediating Roles of Social Support and Exercise Behavior in Hebei Province, China - Luo S; Wu LM; Wang Y; Jin HQ; Zhao YN; Du XF (Clinical Interventions in Aging)
Shan Luo,1 Li Ming Wu,1 Yan Wang,1 Hong Qin Jin,1 Ya Ning Zhao,2 Xiao Fei Du1 1Department of Nursing, Tangshan Vocational & Technical College, Tangshan, Heibei, 063000, People’s Republic of China; 2College of Nursing and Rehabilitation, North China University of Science and Technology, Tangshan, Heibei, 063210, People’s Republic of ChinaCorrespondence: Li Ming Wu, Department of Nursing, Tangshan Vocational & Technical College, Tangshan, Heibei, People’s Republic of China, Email wuliming334@163.comObjective: With China’s rapidly aging population, institutional care for older adults is becoming increasingly common. Spiritual well-being has emerged as a key component of quality elderly care, contributing to emotional resilience, life satisfaction, and positive aging. This study explores the impact of exercise identity on the Spiritual well-being of older adults residing in nursing homes and the mediating roles of perceived social support and exercise behavior.Methods: A survey was conducted on 514 older adults residing in nursing homes using general demographic questionnaires, the Spirituality Index of Well-Being Scale, the Perceived Social Support Scale, the Physical Activity Rating Scale, and the Exercise Identity Scale.Results: The total score of Spiritual well-being among older adults residing in nursing homes was (32.76 ± 7.07). Significant positive correlations were found among exercise identity, perceived social support, exercise behavior, and Spiritual well-being. Perceived social support partially mediated the relationship between exercise identity and Spiritual well-being, with an indirect effect value of 0.237, accounting for 39.6% of the total effect (0.599). Exercise behavior also partially mediated the relationship between exercise identity and Spiritual well-being, with an indirect effect value of 0.201, accounting for 33.5% of the total effect (0.599).Conclusion: Perceived social support and exercise behavior have parallel mediating effects on the relationship between exercise identity and Spiritual well-being of older adults residing in nursing homes. These findings offer a theoretical foundation for developing targeted interventions aimed at enhancing spiritual well-being through improved exercise identity and supportive environments in institutional care settings.Keywords: older adults in nursing homes, exercise identity, spiritual well-being, perceived social support, exercise behavior